Salmonella diarrhea: contributions from the microbiota, the pathogen and the host - Hardt, Wolf-Dietrich (Henry Stewart Talks, 2011)
In Salmonella diarrhea the pathogen engages in a dense network of interactions with the commensal gut microbiota and the host's intestinal mucosa as well as the gut associated immune system, Recent progress has allowed first insights into the molecular mechanisms driving these complex interaction networks